Understanding educational inequalities in sports participation through structurally based resources and individual agency - a sequential mediation analysis - Andrea L. Mudd; Michèlle Bal; Frank J. van Lenthe; Carlijn B. M. Kamphuis (BMC, 2024)
Abstract Educational inequalities in sports participation remain a public health issue in the Netherlands. Combining structurally based resources from Pierre Bourdieu's theory of capital with Amartya Sen's conceptualization of individual agency may offer new insights into the complex mechanisms that drive these inequalities. Specifically, we posited that the way individuals are able to exercise their agency within the structurally based economic, social, and cultural resources they have access to may help explain educational inequalities in sports participation. Data from two waves of the GLOBE study (2014, 2021) were used to test whether two sequential mediators, structurally based resources followed by individual agency, help explain the relationship between educational level and sports participation. Adults aged 25 and older residing in Eindhoven, the Netherlands self-reported highest attained educational level, structurally based resources (economic, social, and embodied cultural capital), individual agency (self-control, perceived choice, and reflexivity), and sports participation. A sequential mediation analysis using structural equation modelling was used to test the direct effect of education on sports participation, the sequential indirect effect through both mediators, and partial indirect effects through each mediator individually. Educational level was positively associated with sports participation. The hypothesized sequential mediation pathway was not supported; educational level was positively associated with structurally based resources and structurally based resources were positively associated with individual agency, but individual agency was not related to sports participation. Though not through individual agency, structurally based resources helped explain educational inequalities in sports participation. Having access to more economic, social, and cultural resources may empower individuals by increasing their agency. This increased agency was not associated with sports participation, which could be because sports participation is not universally valued as a goal. The conceptualization and operationalization of individual agency in the context of sports participation warrants more research. We found that structurally based resources helped explain a substantial portion of educational inequalities in sport, so we propose that policies alleviating more than just economic barriers to sports participation, but also social and cultural barriers, may help reduce educational inequalities in sports participation in the Netherlands.